(3NUNUI GdCef YHQ fXGe GdeYdheGJ aj GWGQ GdOhdI GdMOjKI hGdeYGUQIs - (3cSGH(B, (3eMeO CMeO Ydjs ((3GdEScfOQjIs (3GdecJH GdLGeYj GdMOjKs, 2023)
(3NUNUI GdCef aj EWGQ GdfXe GdSjGSjI GdMOjKI, GdefWdbGJ GdacQjI hGdSjGSjI ddjHQGdjI GdLOjOI, GdWhQ GdLOjO ef GdYdGbGJ GdOhdjI aj EWGQ GGdjHQGdjI GdLOjOI, JGQjN GdJjGQGJ GdacQjI, GdbQGAI GdYOejI ddJGQjN, LPhQ GdacQI GddjHQGdjI GdYQHjI GdLOjOI, JhLgGJ GdQCSeGdjI GdLOjOI aj GdHfjI GdSjGSjI GdYQHjI hQDGgG GdacQjI, JYOjd hXGFa GdOhdI YbH GdJhSY GdQCSeGdj, JOhjd GdLjhT GdhWfjI, GdTQYfI GdCWdSjI, GdJhLg fMh JOhjd GdfRGYGJ GdGLJeGYjI aj EWGQ GdQCSeGdjI GdMOjKI, GdUQGY GdWHbj hefXheJg GdacQjI(B/ (3GdSjGSjI, hMOGfjI GdJWhQ GdQCSeGdj, JWhQ GdfRGYGJ GdGLJeGYjI, hXjaI GdTQWI, fXGe GdTQWI dOi bOeGA GdeUQjjf, fXGe GdTQWI aj YUQ GdHWGdeI, GdTQWI aj YgO GdQheGf, GdTQWI aj YgO GdQShd Udi Gddg Ydjg hSde hGdNdaGA GdQGTOjf, GdTQWI EHGf GdYUQ GdCehj hGdYHGSj, fXGe GdTQWI aj YUQ GdOhdI GdaGWejI hGdCjhHjI hGdYKeGfjI, fXGe GdTQWI JMJ hWCI GdGMJdGd GdGfLdjRj deUQ, GdeYGjjQ GdabgjI ddJejjR Hjf GdVHW GdEOGQj hGdVHW GdbVGFj, QTO GdbQGQ GdTQWj, NUGFU hSeGJ QTO GdbQGQ GdTQWj, GdYdGbI Hjf GdCef hfXGe GdMce, ChLg GdGNJdGa Hjf GdHhdjS GdEOGQj hGdHhdjS GdbVGFj, GdYfGUQ GdechfI ddfXGe GdYGe, SeGJ GdfXGe GdYGe, JOGYjGJ eOdhd GdfXGe GdYGe Ydi hXjaI GdHhdjS, GJNGP GdbQGQ GdTQWj YHQ fXGe GdeYdheGJ, fXe GdeYdheGJ HhRGQI GdOGNdjI GdeUQjI, GdeDKQGJ GdNGQLjI aj GdbQGQ GdTQWj, eaghe hOhQ GdCef aj GdfXGe GdOjebQGWj, eOi GecGfjI JWHjb eHOC OjebQGWjI GdEOGQI Ydi hXjaI GdHhdjS, fXGe GdHhdjS GdeQcRj hGddGeQcRj, eYGdLI GdLQGFe GdCNdGbjI GdSdhcjI OGNd LgGR GdTQWI, egGe GdHhdjS aj EWGQ GdOhdI GdMOjKI hGdeYGUQI(B.s
Keywords: (3GdCefs; (3GdCef Gdbhejs; (3GdTQWIs; (3GdTQWI(B- (3eUQs; (3NUNUI GdCefs